DIAD as a promoter for cyanomethylation of alkenes by Cu catalysis. Issue 11 (11th March 2015) - Tang, Shi; Li, Shu-Hua; Li, Zhi-Hao; Zhou, Dong; Sheng, Rui-Long
Graphical abstract: Abstract: A novel and practical DIAD-promoted oxidative cyanomethylation of alkenes with acetonitrile by copper catalysis was developed, in which oxindoles bearing a nitrile moiety at the 3-position were synthesized efficiently via dual C–H bond cleavage of an arene and acetonitrile. This protocol demonstrated that DIAD served as a new promoter instead of commonly encountered AgF or base for the Csp3 –H functionalization of acetonitrile for the first time.